Acute heavy alcohol intake increases silent myocardial ischaemia in patients with stable angina pectoris. Issue 6 (June 1996) - Rossinen, J.; Partanen, J.; Koskinen, P.; Toivonen, L.; Kupari, M.; Nieminen, M. S.
Abstract : OBJECTIVE: To evaluate the effect of acute alcohol ingestion on myocardial ischaemia in patients with coronary heart disease and stable angina. DESIGN: Randomised crossover study using fruit juice with and without ethanol. SETTING: Division of cardiology in a university hospital. PATIENTS: 20 patients with stable exertional angina and > or = 50% luminal diameter narrowing of at least one major coronary artery. INTERVENTIONS: Each patient was studied on two separate days, once after administration of 1.25 g of ethanol per kilogram of body weight diluted to 15% in juice, and once after an equivalent volume of juice; both tests were in the evening and lasted 90 minutes. The patients were scheduled to have 8 periods of walking for 10 min according to a time table. An ambulatory electrocardiogram and the occurrence of anginal attacks were recorded and blood pressure and blood ethanol concentration were measured until the next morning. RESULTS: The blood ethanol concentration (mean (SD)) rose to 28.8 mmol/l (1.3 (0.4)/1000). Alcohol raised the systolic blood pressure from 132 (16) to 141 (14) mm Hg (P < 0.05 compared with juice). The mean heart rate increased from 57 (7) to 64 (8) beats/min (P < 0.05) for 13 hours after ethanol ingestion compared with juice. The total duration of ischaemia during the ethanol test was 3.5 (median, range 0-80) min, compared with 0 (range 0-67) min for the juice test (P < 0.05). The difference resulted mainly from more silent ischaemia after ethanol ingestion (2.3 (0-80) v 0 (0-67) min; P < 0.05). The ST segment depression time integral increased during the ethanol test (4.4 (0-170) mm x min) relative to that during the juice test (0 (0-103) mm x min; P < 0.01) and especially during the following 13 hours after alcohol (3.5 (0-123) mm x min) compared with juice (0 (0-67) mm x min; P < 0.005). There were no changes in the number, duration, or ST segment depression time integral of the episodes of symptomatic angina, indicating that ethanol augmented the appearance of silent ischaemia. CONCLUSIONS: Acute heavy ethanol drinking aggravates myocardial ischaemia in patients with stable angina pectoris.